Enhancing High School Students’ Cognitive and Affective Empathy through a Deep Learning-Based Multicultural History Learning Model - Sumargono; Sinaga, Risma Margareta; Perdana, Yusuf; Deviana; Risthy Puji Handayani; Ardian Fahri (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study investigates the effectiveness of a Multicultural Learning Model Incorporating Historical Events (MLMIHE), implemented through a pedagogical deep learning approach, in simultaneously enhancing the cognitive and affective dimensions of historical empathy among Indonesian high school students. A quasi-experimental Non-Equivalent Control Group Design was employed across three purposively selected senior high schools in Lampung Province (N = 202, Grade XI). The experimental group (n = 99) received instruction through the five-phase MLMIHE model, while the control group (n = 103) continued with established conventional approaches. Both groups completed validated pre- and post-intervention assessments of cognitive and affective empathy. Inferential analyses comprised paired-samples and independent-samples t-tests, normalized gain (N-Gain) scoring, and Cohen’s d effect size estimation. The experimental group demonstrated statistically significant improvements in cognitive empathy (t = 8.862, p < .001; N-Gain = 0.91; d = 1.27) and affective empathy (t = 9.196, p < .001; N-Gain = 0.40; d = 1.57) relative to the control group, with large-to-very-large effect sizes across all three school sites. Student response surveys indicated high model acceptance (M = 84%). The MLMIHE model, grounded in constructivist and multicultural educational theory, constitutes an empirically validated instructional alternative to conventional history pedagogy and effectively cultivates both dimensions of historical empathy within Indonesia’s culturally plural context. Implications for history curriculum design and teacher professional development are discussed.